Cicerono santykis su graikais ir jų kultūra - Kučinskienė, Audronė (Literatūra, 2015)
In this article certain aspects of the following problems are discussed: Cicero’s controversial attitude to the Greeks; the traits of the Greek national character as portrayed in Cicero’s works, as well as Cicero’s ambivalent appreciation of the Greek art and literature.The principle of odi et amo clearly shows itself in Cicero’s attitude to the Greeks, both his contemporaries and the ancients, their art and literature. Cicero felt he owed an enormous debt to his Greek education, considering himself as an inheritor of their culture, and yet he denounced it at every opportunity and tried to emphasise the superiority of the Roman ancestors against the Greeks. He greatly appreciated Greek literature and yet he wished he could manage without it, because the Greek literary standards made him aware of what Roman literature should be.The main national traits ascribed to the Greeks in Cicero’s speeches ant letters are the lack of trustworthiness (fides), unreliability (levitas), and vanity (vanitas) as opposed to the Roman dignity (dignitas) and gravity (gravitas).We argue that in evaluating Cicero’s attitude to the Greeks it is especially important to take into account the genre of those Cicero’s works from which we derive our knowledge about his views. His speeches as well as his treatises are intended for the public audience, so the author tries to portray himself in accordance with the public expectations, while his private correspondence, especially the letters to Atticus, reveals his personal views, not restricted by the public opinion. As we have shown in this article, in his speeches Cicero tries to conceal his expertise in the Greek art and literature, as this would not fit his Roman dignity. On the other hand, in his private life, as it appears from his letters to Atticus, he eagerly seeks pieces of Greek art to decorate his villas.This seeming inconsistency of Cicero’s views, however, can be partly explained as follows. It is to be borne in mind that Cicero’s criterion for the selection of the Greek statues is neither their artistic value nor the renown of the sculptor, but their suitability for the particular place they are intended to decorate. This principle of suitability for the purpose (decorum, aptum, pV#pon) is also claimed by Cicero to be one of the fundamentals of the art of rhetoric (Cic. Or. 70; De orat. III. 210). In another words, the selection and the functional application of the Greek pieces of art in his villas have the purpose to reveal the same Roman dignity, which Cicero declares in his speeches.